Is There Any Association between PEEP and Upper Extremity DVT? - Farah Al-Saffar; Ena Gupta; Furqan Siddiqi; Muhammad Faisal; Lisa M. Jones; Vandana Seeram; Mariam Louis; James D. Cury; Abubakr A. Bajwa; Adil Shujaat (Critical Care Research and Practice)
Background. We hypothesized that positive end-exploratory pressure (PEEP) may promote venous stasis in the upper extremities and predispose to upper extremity deep vein thrombosis (UEDVT). Methods. We performed a retrospective case control study of medical intensive care unit patients who required mechanical ventilation (MV) for >72 hours and underwent duplex ultrasound of their upper veins for suspected DVT between January 2011 and December 2013. Results. UEDVT was found in 32 (28.5%) of 112 patients. Nineteen (67.8%) had a central venous catheter on the same side. The mean ± SD duration of MV was 13.2±9.5 days. Average PEEP was 7.13±2.97 cm H2O. Average PEEP was ≥10 cm H2O in 23 (20.5%) patients. Congestive heart failure (CHF) significantly increased the odds of UEDVT (OR 4.53, 95% CI 1.13–18.11; P=0.03) whereas longer duration of MV (≥13 vs. <13 days) significantly reduced it (OR 0.29, 95% CI 0.11–0.8; P=0.02). Morbid obesity showed a trend towards significance (OR 3.82, 95% CI 0.95–15.4; P=0.06). Neither PEEP nor any of the other analyzed predictors was associated with UEDVT. Conclusions. There is no association between PEEP and UEDVT. CHF may predispose to UEDVT whereas the risk of UEDVT declines with longer duration of MV.